Social capital and the mediating effect of competitive advantage on the performance of women-owned enterprise. - Rajennd Muniady (2016)
Entrepreneurship and social capital is hard to be separated as entrepreneurial activities are embedded in networks of social relationship. This study is motivated by the inconclusiveness of social capital research in developing countries and how it affects the performance of micro-enterprise owned by women entrepreneurs. This study used social capital theory as a base and examined how social capital as an independent variable effects competitive advantage, which is the mediating variable and micro- enterprise performance which is the dependent variable. The present study looked into the formation of social capital and how it affects competitive advantage and micro- enterprise performance, and the mediating effect of competitive advantage between social capital and micro-enterprise performance. This study used a cross-sectional design and quantitative data was collected through structured interview from randomly selected 417 women micro-entrepreneurs in Peninsular Malaysia, who are listed in SME Corporation. Data was analysed by using SPSS and the hierarchical and measurement model was tested using partial least squares (PLS) technique. The findings suggest that all three dimensions (i.e., relational, cognitive and structural social capital) have a significant positive effect on the formation of social capital. Among the three dimensions of social capital, structural dimension which includes network density and ties has the biggest effect on social capital formation. Social capital is proved to affect competitive advantage and micro-enterprise performance positively and is significant. Baron and Kenny (1986) approach proved that competitive advantage partially mediates the relationship between social capital and micro-enterprise performance. This study provides empirical evidence on the effects of social capital on competitive advantage and micro-enterprise performance thus proving how important is social capital to women micro-entrepreneurs. Women entrepreneurs should focus on improving their social capital by building trust and quality relationship; investing time in building network and understanding values and norms among key business players. Government and development agencies aiming to improve women involvement in entrepreneurship and economic development should work towards creating industry specific platforms for women entrepreneurs. Through these platforms, micro-entrepreneurs would be able to share and receive ideas and experiences. It further allows building of trust, networks and understanding. This study recommends future researchers to test the model used in this study in different settings and backgrounds to provide empirical verification in predicting competitive advantage and firm performance.